Analisis Manajemen Waktu Mahasiswa terhadap Produktivitas Akademik pada Mahasiswa Pendidikan Ekonomi Universitas Jambi - Nur Alyah; Syahdikin Syahdikin; Fadilla Ulfah; Novia Sri Dwijayanti (Jurnal Ekonomi dan Pembangunan Indonesia, 2026)
This study aims to analyze student time management and its relationship to academic productivity among students in the Economics Education Study Program, Jambi University, class of 2023. This study used a qualitative approach with data collection techniques through in-depth interviews with a number of students selected purposively. The results showed that most students were unable to manage their time optimally, as reflected in the habit of procrastinating on assignments, a lack of structured planning, and an imbalance between academic and non-academic activities. Many students tended to work on assignments only close to the deadline and found it difficult to maintain a consistent schedule. Conversely, students who had a more structured time plan, such as compiling daily to-do lists and setting priorities, demonstrated better academic productivity. They were able to complete assignments on time, produce better quality work, and were more active in the learning process and class discussions. This study confirms that effective time management plays a crucial role in improving student academic productivity, both in terms of the quality of work results and the timeliness of assignment completion. Therefore, more intensive efforts are needed to increase students' awareness and skills in time management, so they can achieve optimal learning outcomes, reduce stress levels, and face academic demands more efficiently. In this context, developing good time management strategies is essential to help students maximize their academic potential.